1980
DOI: 10.1086/337169
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in the Walls of Ripening Avocados: Transmission, Scanning, and Freeze Fracture Microscopy

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 24 publications
4
33
1
Order By: Relevance
“…In the case of avocados, detailed ultrastructural studies have been made of the cell wall (Platt-Aloia et al 1980) and of the cell wall contents (Platt-Aloia and Thomson 1981) in ripening fruit. During ripening, it was found that the middle lamella begins to disappear, with pectin removal from the matrix of the cell walls.…”
Section: B Structural Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of avocados, detailed ultrastructural studies have been made of the cell wall (Platt-Aloia et al 1980) and of the cell wall contents (Platt-Aloia and Thomson 1981) in ripening fruit. During ripening, it was found that the middle lamella begins to disappear, with pectin removal from the matrix of the cell walls.…”
Section: B Structural Changesmentioning
confidence: 99%
“…It was found that the enzyme is a (1 -cu4)-/3-D-glucanase, and that the activity is limited to hydrolysing /3-D-glucans of four or more glucosyl residues. These authors therefore contend that the solubilization of the cell walls during softening as seen by Platt-Aloia et al (1980) cannot be due to cellulase alone, and they propose a different role forcellulase. Hatfield and Nevins (1986) consider that xyloglucans or cellulose fibrils may be hydrolysed, which would be consistent with microscopic observations of cellulose xyloglucans, or cellulose fibrils may be hydrolysed, which would be consistent with microscopic observations of cellulose fibrillar changes.…”
Section: Enzymesmentioning
confidence: 99%
“…Ripening of avocado fruit is accompanied by softening of the fruit which is believed to be due to an extensive breakdown of its cell wall (20). Fruit softening is associated with an increase in the activities of hydrolytic enzymes such as cellulase and polygalacturonase (1,6,14,19).…”
mentioning
confidence: 99%
“…Fruit softening is associated with an increase in the activities of hydrolytic enzymes such as cellulase and polygalacturonase (1,6,14,19). Although an increase in avocado cellulase activity correlates well with softening (1) and changes in the structural integrity of the cell wall (19,20), elucidation of its role in vivo is far from complete (12).…”
mentioning
confidence: 99%
“…Softening in avocado fruits is accompanied by an extensive breakdown of the cell wall (22), which is associated with an increase in the activities of hydrolytic enzymes such as cellulase, polygalacturonase, and acid phosphatase (3,21,23). Information concerning the synthesis and regulation of polygalacturonase and acid phosphatase during avocado ripening is very limited.…”
mentioning
confidence: 99%